Brand Adaptation Strategy in Global Marketing : A Study Qualitative in Multinational Companies - Taufiqurrahman Taufiqurrahman; Nuri Aslami; Kamran Abdullayev (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze brand adaptation strategies employed by multinational companies in addressing global marketing challenges, particularly in the context of cultural differences, consumer preferences, and regulatory variations across countries. Using a qualitative approach with a case study method, data were collected through in-depth interviews with marketing managers and document analysis related to corporate branding strategies. The findings reveal that multinational companies adopt a flexible brand adaptation approach by adjusting product elements, marketing communications, and brand values to align with local market characteristics while maintaining their global identity. These findings highlight that balancing global brand consistency with local market adaptation is a key factor in the success of global marketing strategies.